Implementation of Legal Protection for Creditors for Defaulting Customers with Motorized Vehicle Ownership Book Guarantees - Nadila Miftahul Jannah; Sri Maharani Mardianingrum T. V. M. (Widya Pranata Hukum : Jurnal Kajian dan Penelitian Hukum, 2023)
A customer who defaults on a credit agreement basically harms the creditor. The purpose of this research is to explore the implementation of legal protection for creditors for customers who default on credit agreements by guaranteeing Motor Vehicle Ownership Books. The type of research used is empirical juridical with field studies at PT. BPR Bank Pasar Bhakti Sidoarjo. The results of the study show that the implementation of legal protection includes preventive legal protection and repressive legal protection. Guaranteed motorbike taxis will be burdened with fiduciary guarantees which are used as a form of legal certainty and can protect creditors when bad credit occurs. Repressive legal protection taken in resolving bad credit disputes is by credit restructuring first. If it is not successful, the creditor executes the collateral object which will later be sold privately to pay off the debtor's debt to the creditor.